1990
DOI: 10.1002/1097-0355(199023)11:3<259::aid-imhj2280110308>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Internal representational models of attachment relationships

Abstract: Bowlby's notion of internal representational models is explored with the purpose of clarifying the nature of such models. Distinctions are made among the concepts of (a) focus, (b) memory systems, (c) content, (d) cognitive function, (e) meta‐structure, (f) quality of attachment, (g) behavioral strategies, and (h) attitude toward attachment. New terms are offered for familiar concepts, such as defended insecure quality of attachment. New meanings are given for familiar terms, such as working model and balanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
138
1
16

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(161 citation statements)
references
References 24 publications
6
138
1
16
Order By: Relevance
“…It may be that such cognitive abilities are an important step in the development of IWMs. The capacities acquired to synthesize and create non-verbal concepts can be very helpful for the two main functions of IWMs, i.e., the interpretation and the prediction of external events and others' behavior (Crittenden, 1990). A child displaying good reasoning abilities would therefore be more likely to create and refer to secure IWMs.…”
Section: Stievenart Et Al 63mentioning
confidence: 99%
See 1 more Smart Citation
“…It may be that such cognitive abilities are an important step in the development of IWMs. The capacities acquired to synthesize and create non-verbal concepts can be very helpful for the two main functions of IWMs, i.e., the interpretation and the prediction of external events and others' behavior (Crittenden, 1990). A child displaying good reasoning abilities would therefore be more likely to create and refer to secure IWMs.…”
Section: Stievenart Et Al 63mentioning
confidence: 99%
“…All researchers dealing with IWMs agree on the importance of their dynamic character. For instance, Atkinson (Atkinson et al, 1999, p. 46) defined IWMs as ''active constructions that are restructured in response to environmental, affective and cognitive change '' and Crittenden (1990) suggested that models could be said to be ''open'' if the subject could make new interpretations and predictions, whereas they are ''closed'' if all behaviors are interpreted in terms of existing models. On the other hand, ''working'' models allow cognitive manipulations, whereas ''non-working'' models do not.…”
mentioning
confidence: 99%
“…Based on previous work indicating reciprocal relations between preschoolers' IQ and attachment representations (Stievenart, Meunier, Van de Moortele, & Roskam, 2012;, both reasoning and verbal IQ are hypothesized to have an influence on the developmental course of attachment. Children with higher IQ are expected to be more likely to maintain their secure and organized previous attachment representations in the face of modifications in parenting because they have the ability to cope with new relational and social information (Crittenden, 1990). Conversely, modifications in parenting would be more likely to disturb the attachment representations of children with lower IQ because of their inability to integrate new social and relational information without a radical transformation of their attachment representations (Crittenden, 1990).…”
mentioning
confidence: 99%
“…A number of studies (Cassidy, 1994;Crittenden, 1990;Crittenden, 2006;Feeney & Noller, 1996;Lyons-Ruth, Bronfman, & Atwood, 1999) suggest that each of the different attachment groups is characterized by a specific parenting profile. Based on these findings, we expected that, compared to mothers of insecure children, mothers of the secure type would report a significantly higher tendency to serve as a secure base for the child, and that in difficult circumstances these mothers would report a higher tendency to validate their children's negative emotional states, a higher tendency to respond with comforting behaviors when needed, and a higher ability to help children cope with their problems.…”
Section: Semi-projective Doll Play Techniques Attachment Classificatimentioning
confidence: 99%